2010
DOI: 10.1063/1.3284660
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency green, yellow, and amber emission from InGaN/GaN dot-in-a-wire heterostructures on Si(111)

Abstract: The authors report on the achievement of nearly defect-free, vertically aligned InGaN/GaN dot-in-a-wire nanoscale heterostructures grown directly on Si(111) substrates by molecular beam epitaxy. Strong green, yellow, and amber emission, with a room temperature internal quantum efficiency of ∼45% of that measured at low temperature (∼10 K), was achieved. Detailed structural and optical studies further confirm that the emission characteristics are strongly influenced by the presence of In-rich nanoclusters, form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
106
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 19 publications
6
106
1
Order By: Relevance
“…GaN nanowires then form spontaneously on various substrates without the need of any metal droplets that are required for many other semiconductor materials to induce the vapor-liquid-solid growth of one-dimensional nanostructures [4][5][6]. One of the distinct advantages of the spontaneous formation and subsequent uniaxial growth of GaN nanowires is the possibility to realize abrupt axial heterojunctions between different III-N compounds by simply switching the group III supply [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…GaN nanowires then form spontaneously on various substrates without the need of any metal droplets that are required for many other semiconductor materials to induce the vapor-liquid-solid growth of one-dimensional nanostructures [4][5][6]. One of the distinct advantages of the spontaneous formation and subsequent uniaxial growth of GaN nanowires is the possibility to realize abrupt axial heterojunctions between different III-N compounds by simply switching the group III supply [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This technique [12][13][14][15] and also vapor phase deposition methods [16][17][18] have been used to produce InGaN NCs [13,14,16,18] and nanocolumnar InGaN/GaN quantum heterostructures [12,15,17], providing efficient room-temperature (RT) light emission, probably resulting from carrier localization, as already well-known for InGaN alloys [19]. Emission over the entire visible spectrum was achieved by control of the In incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas growth of GaN on a 2D AlN layer invariably results in the formation of GaN QDs according to the SK growth mode, it appears that NW morphology indeed leads to the growth of GaN NDs. In the case of a large in-plane lattice mismatch insufficiently accommodated by NW geometry, the formation of 3D islands is preferred, as illustrated in Figure 2c by a picture exemplifying the growth of high In content InGaN islands on top of a GaN NW [19,20]. these predictions, it has been found that individual InGaN dot-in-NWs, such as the ones shown in Figure 2c, indeed exhibit an In content gradient from the base to the top, related to the easy elastic deformation of the tip of the island.…”
Section: The Case Of Spontaneously Nucleated Nws Grown By Molecular Bmentioning
confidence: 99%